MINORITY SHAREHOLDERS' LEGAL COVER ON CLOSED COMPANY MERGERS - Marlina E. Pakpahan (NOMOI Law Review, 2022)
Minority shareholders is one of the stakeholders along with other stakeholders and minority shareholders are also the parties reply carries the coffers for the company. This is what interests should be protected by law. The methods used in this study is a research method, a normative legal method by means of data collection based on the study of librarianship (library search) that is by way of secondary data in the form of researching materials such as primary law scientific books, legislation, and the data that is retrieved by accessing the internet related to this research. The results from this research that the appraisal of the implementation of rights is one's